Trauma context exerts intergenerational effects on child mental health via DNA methylation - Stefanie Pilkay; Andie Riffer; Andrew Carroll (Epigenetics)
Many people experience traumatic or negative events, but few develop mental health issues as a result. This study investigated whether newborn DNA methylation (DNAm) previously associated with maternal childhood physical abuse by her father affected the child’s mental health and physical growth, as well as whether it mediated or moderated developmental outcomes. Methods: Study sample (N = 903) and data came from Bristol University’s Avon Longitudinal Study of Parents and Children. DNAm was measured in cord blood at birth. DNAm data was preprocessed, normalized, and quality controlled before subsetting to 60 CpG sites of interest from previous research. Linear regression analysis examined newborn DNAm and child development outcome associations. Sobel test examined the mediating relationship between mother’s history of childhood abuse by father, newborn targeted gene DNAm of significant CpG sites, and child’s mental health and physical growth. Moderation analyses examined the interaction effects between the significant CpG sites and mothers’ physical abuse by their fathers on child’s mental health and physical growth. Results: Full cohort analyses showed that newborn DNAm of several different CpG sites associates with separation anxiety, fear, and unhappy/tearful presentations in children aged 6–7 y. Sex-specific associations emerged with boys showing associations with anxiety and fear, and girls showing associations with fear and unhappiness. In boys only, cord blood DNAm mediates the effect of maternal childhood trauma on offspring mental health. No moderation effects emerged. Conclusion: Intergenerational effects of mother’s relationship to her abuser present in newborn DNAm associate with 7-year-old child’s mental health, show sex-specific effects, and newborn DNAm does mediate maternal childhood trauma effects on offspring mental health in early-life.